High-grade Transformation/Dedifferentiation in Salivary Gland Carcinomas: Occurrence Across Subtypes and Clinical Significance - Skalova, Alena; Leivo, Ilmo; Hellquist, Henrik; Agaimy, Abbas; Simpson, Roderick H.W.; Stenman, Göran; Vander Poorten, Vincent; Bishop, Justin A.; Franchi, Alessandro; Hernandez-Prera, Juan C.; Slouka, David; Willems, Stefan M.; et al. (Advances in Anatomic Pathology, 2021)
High-grade transformation (HGT) or dedifferentiation has been described in a variety of salivary gland carcinomas, including acinic cell carcinoma, secretory carcinoma, adenoid cystic carcinoma, epithelial-myoepithelial carcinoma, polymorphous adenocarcinoma, low-grade mucoepidermoid carcinoma, and hyalinizing clear cell carcinoma. High-grade (HG) transformed tumors are composed of a conventional low-grade component characterized by specific microscopic and immunohistochemical features for the given entity, intermingled with or juxtaposed to areas of HG morphology. This is usually either poorly differentiated adenocarcinoma, carcinoma not otherwise specified, or undifferentiated carcinoma, in which the original line of differentiation is lost. The HG component is composed of solid nests of anaplastic cells with large vesicular pleomorphic nuclei, prominent nucleoli, and abundant cytoplasm. Frequent mitoses and extensive necrosis may be present. The Ki-67 labeling index is consistently higher in the HG component. The molecular genetic mechanisms responsible for HGT of salivary gland carcinomas are largely unknown, though p53 inactivation and human epidermal growth factor receptor 2 overexpression and/or gene amplification have been demonstrated in the HG component in a few examples, the frequency varies for each histologic type. Salivary gland carcinomas with HGT are more aggressive than conventional carcinomas, with a higher local recurrence rate and a poorer prognosis. They have a high propensity for cervical lymph node metastasis suggesting a need for a wider resection and neck dissection. HGT of salivary gland carcinoma can occur either at initial presentation or less commonly at the time of recurrence, sometimes following postoperative radiotherapy. The potential for HGT in almost any type of salivary gland carcinoma warrants a thorough sampling of all salivary gland malignancies to prevent oversight of a HG component.
CRIS-Team Scopus Importer:2021-04-19